Oral Contraceptives as risk factors for cervical intraepithelial neoplasia - WANI, PARAS; AHMAD, MASHKOOR; M J, SIDDIQUE; WANI, GAZANFER (The Indian Journal of Animal Reproduction, 2007)
A Clinic initiated community oriented cross sectional study on, "A Study of efficacy of VIA Technique in Screening of Carcinoma of cervix in Situ" was conducted by department Preventive and Social Medicine, J amia Hamdard, New Delhi. Analysis of positive Pap smears and VIA (Visual inspection with acetic acid) with use of oral contraceptives was done using chi square test at degree of freedom I and C.l 95%. Probability of positive Pap smears and VIA in subjects with use of oral Contraceptive practices was more.